An equation is shown.

(2x - 3) + [4x(3x + 2)]

Which expression is equivalent to the given expression?

A,.) 9x - 1

B.) 14x + 5

C.) 12x² + 2x - 1

D.) 12x² + 10x - 3

(2x - 3) + [4x(3x + 2)]

Which expression is equivalent to the given expression?

A,.) 9x - 1

B.) 14x + 5

C.) 12x² + 2x - 1

D.) 12x² + 10x - 3

(2x - 3) + [4x(3x + 2)]

= 2x - 3 + (12x² + 8x) {removed first set of parentheses and used distributive property inside brackets}

= 2x - 3 + 12x² + 8x {removed parentheses}

= 12x² + 10x - 3 {combined like terms}

= 2x - 3 + (12x² + 8x) {removed first set of parentheses and used distributive property inside brackets}

= 2x - 3 + 12x² + 8x {removed parentheses}

= 12x² + 10x - 3 {combined like terms}

**D.) 12x² + 10x - 3****Ask Algebra House**